Fundamentals of Strategy - Whittington, Richard; Angwin, Duncan; Regnér, Patrick; Johnson, Gerry; Scholes, Kevan (Pearson International Content, 2023)
Understand and apply the essential concepts and techniques of strategy. Fundamentals of Strategy, 6th Edition is a concise and easy-to-follow introduction to the core issues and techniques of strategy from the author team of the market-leading Exploring Strategy. This latest edition is renewed and revised to reflect contemporary strategic issues with increased emphasis on business ecosystems, platforms, purpose and implementation. Each chapter includes a diverse range of international examples from across sectors and industries, including start-ups, non-profits, and multinationals. End-of-chapter case studies further help you to connect theories to real-world scenarios. The nine chapters provide an accessible introductory analysis of the 'strategic position' and 'strategic choices' facing contemporary organisations. Topics explored include macro-environmental and industry analysis, strategic capability, stakeholders and culture as well as a discussion of business-level strategies, business models, international strategies, strategic entrepreneurship, innovation and mergers and acquisitions. The final chapter, 'Strategy in action' addresses implementation issues such as organisational structure, managerial systems and strategic change. In addition, new supporting content at the end of the book on ‘Working with strategy' for case study analysis and presentation further provides practical tools to help you develop your strategic analysis and communication skills. As a result, this textbook is ideal for undergraduate and MBA students who study strategy analysis-related courses or strategy as part of a wider degree in areas such as science or engineering.